Tandem-X: Mission and Science - Hajnsek, Irena; Moreira, Alberto; Zink, Manfred; Buckreuss, Stefan; Kraus, Thomas; Bachmann, Markus; Busche, Thomas Edmund (2021 IEEE International Geoscience and Remote Sensing Symposium IGARSS, 2021)
The paper provides an up to date overview of the German TanDEM-X satellite mission status and its ongoing science activities. In June 2020 TanDEM-X reached his 10 years of successful operation - a view forward will be presented in the final paper. The global digital elevation model (DEM) of TanDEM-X became available in 2016 and surpassed all expectations: It has 99.9% coverage, 12-m posting, absolute height accuracy of approximately 1 m and a relative height error (standard deviation) of 0.8 m. This unique data set has been available since then for commercial and scientific applications. Last year, a low-resolution version of the global digital elevation model with 90-m posting has been released for free download for scientific applications. Since 2017 new interferometric acquisitions have been started with the goal to generate a global change layer which will register all the changes of the Earth topography occurred since the first acquisitions of TanDEM-X. The data collection for the global change layer will be ready by the end of 2020. Currently, a new science phase of TanDEM-X is running with a focus on interferometric acquisitions over forest, ice sheets and permafrost regions